OPTIMALISASI EDUKASI KESEHATAN REPRODUKSI UNTUK MENINGKATKAN PENGETAHUAN REMAJA DALAM MENGENDALIKAN RISIKO KEHAMILAN - Weny Anggraeni Adhysti; Immawanti, Immawanti; Evawati, Evawati; Muzdalia, Ika; Yuliani, Eva; Nurhidayah, Nurhidayah (Jurnal Kesehatan Marendeng, 2025)
Adolescent pregnancy is defined as pregnancy occurring in females aged 14–19 years, whether married or unmarried. This study aims to determine the effect of reproductive health education on adolescents' knowledge of pregnancy risk control using the Focus Group Discussion (FGD) method. The study employed a quantitative approach with a quasi-experimental design and a one-group pretest-posttest research design. A total of 49 students from SMA DHI Mapilli were selected using stratified random sampling. Educational intervention was provided through FGD sessions, followed by measurements of knowledge before and after the intervention. Analysis using the Marginal Homogeneity test showed a significance value of 0.000 (p < 0.05), indicating a significant difference in knowledge levels before and after the education. Therefore, it can be concluded that reproductive health education through the FGD method is effective in increasing adolescents' knowledge about controlling the risks of pregnancy. This study emphasizes the importance of group discussion-based educational interventions as a strategy for promoting reproductive health among adolescents.